Radial thermal expansion of single-walled carbon nanotube bundles at low temperatures - Dolbin, A.V.; Esel`son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Popov, S.N.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
For the first time the linear coefficient of the radial thermal expansion has been measured on a system of SWNT bundles at low temperatures (2.2–120 K). The measurements were performed using a dilatometer with a sensitivity of 2·10–9 cm. The cylindrical sample 7 mm high and 10 mm in diameter was obtained by compressing powder. The resulting bundles of the nanotubes were oriented perpendicular to the sample axis. The starting powder contained over 90% of SWNTs with the outer diameter 1.1 nm, the length varying within 5–30 mm. The change of sign of the radial thermal expansion coefficient at 5.5 K was observed.